THU0603 IGG4-RELATED SINGLE-ORGAN DISEASE: IMMUNOSUPPRESSION NEEDED AFTER COMPLETE RESECTION? A CASE REPORT AN BRIEF LITERATURE REVIEW. (2nd June 2020) - Schirmer, J.; Seeger, M.; Schulte, D.; Laudes, M.; Schreiber, S.; Hoyer, B. F.
Abstract : Background: IgG4-related disease (IgG4-RD) is a polymorphic autoimmune disease leading to tumourous swelling and/or fibrosis of affected organs. Riedel's thyroiditis is – besides chronic periaortitis, Mikulicz Syndrome and many others – an organ manifestation of IgG4-RD that has been thought to be an independent disease for a long time. About 40% of patients have single organ IgG4-RD while the others suffer from multisystemic disease [1]. Objectives: Glucocorticoids, sometimes combined with other immunosuppressives are the standard treatment of IgG4-RD, in some situations (e.g. mechanical complications or suspected malignancy) surgery may be necessary but little is known about the management of fully resected single-organ IgG4-RD [1]. Methods: We report a case of single-organ IgG4-RD (Riedel's thyroiditis) after complete resection and perform a brief review of the literature to guide clinical management in this situation. Results: A woman (51 y) with pre-existing Hashimoto's thyroiditis (thyroid peroxidase antibody positive) developed a rapidly growing struma with very firm consistency (not allowing fine needle biopsy). Besides slightly increased C-reactive protein (5, 3 mg/l) there was no laboratory sign suggestive for IgG4-RD (normal serum IgG4, complement, eosinophils and IgE). Within 4 months the patient suffered from hoarseness and progredient dyspnea. Surgical thyroidectomy was performed and histopathology revealed IgG4-related Riedel's thyroiditis with extensive (storiform) fibrosis, a dense lymphoplasmacytic infiltrate, obliterative phlebitis, eosinophilia and 13 IgG4-positive plasma cells per high power field. After referral to our department a comprehensive work-up showed no signs of other manifestations of IgG4-RD. Treatment with glucocorticoids is clearly recommended for patients with symptomatic IgG4-RD in an international consensus statement, whereas "watchful waiting" may be appropriate in some cases of asymptomatic or mild disease. While some highly fibrotic lesions may not respond well to glucocorticoids and may require surgical intervention, no clear guidance is available for the management of fully resected single organ IgG4-RD [2]. A brief review of the literature revealed that few cases of single-organ IgG4-RD remaining in remission after resection without medical treatment have been reported e.g. IgG4-related cholecystitis, autoimmune-pancreatitis, tumours of the intestinal tract, lung, thymus, meninges, paravertebral space and others [3–9]. After discussion of the options with the patient no systemic immunosuppression was given under close follow up without signs of relapse in clinical examinations, laboratory or imaging during the first 6 months. Conclusion: Limited evidence from case reports suggests that a "watchful waiting" strategy without systemic immunosuppressive treatment may be reasonable in some cases of single-organ IgG4-RD after the affected organ was completely resected (e.g. due to mechanical complications or suspected malignoma). However, close follow-up monitoring should be applied due to the risk of relapse or development of new organ manifestations. References: [1]Brito-Zerón et al. Best Pract. Res. Clin. Rheumatol. 2016 [2]Khosroshahi et al. Arthritis Rheumatol. 2015 [3]Takahashi et al. Surg. Case Rep. 2015 [4]Akbari et al. ACG Case Rep. J. 2018 [5]Oda et al. Thorac. Cancer 2019 [6]Nambirajan et al. Childs Nerv. Syst. ChNS Off. J. Int. Soc. Pediatr. Neurosurg. 2019 [7]Uchida et al. Asian J. Endosc. Surg. 2018 [8]Hart et al. Mod. Pathol. Off. J. U. S. Can. Acad. Pathol. Inc 2015 [9]Kim et al. Tuberc. Respir. Dis. 2014 Disclosure of Interests: Jan Schirmer: None declared, Marcus Seeger: None declared, Dominik Schulte Paid instructor for: Ferring, Speakers bureau: Amgen, Astra Zeneca, Braun, Fresenius, Ipsen, Johnson & Johnson, Lilly, MSD, Novartis, Novo Nordisk, Sanofi, Matthias Laudes Speakers bureau: Roche, Sanofi, Chugai, Stefan Schreiber Consultant of: AbbVie, Arena, BMS, Biogen, Celltrion, Celgene, IMAB, Gilead, MSD, Mylan, Pfizer, Fresenius, Janssen, Takeda, Theravance, provention Bio, Protagonist and Falk, Bimba F. Hoyer: None declared